Brazen - Haart, Julia, 1971- (New York : Crown, 2022)
"A riveting, inspiring memoir of one woman's escape from an extremist religious sect and an extraordinary rise from housewife to shoe designer, to CEO and co-owner of the modeling agency Elite World Group. Ever since she was a child, every aspect of Julia Haart's life-what she wore, what she ate, what she thought-was controlled by the dictates of ultra-Orthodox Judaism. At nineteen, after a lifetime spent caring for her seven younger siblings, she was married off to a man she barely knew. For the next twenty-three years, he would rule her life. Eventually, when Haart's younger daughter, Miriam, started to question why she wasn't allowed to sing, run, or ride a bike, Haart reached a breaking point. She knew that if she didn't find a way to leave, her daughters would be forced into the same unending servitude that had imprisoned her. So Haart created a double life. In the ultra-Orthodox world, clothing has one purpose-to cover the body, head to toe-and giving any thought to one's appearance beyond that is considered sinful, an affront to God. But when no one was looking, Haart would pore over fashion magazines and sketch designs for the clothes she dreamed about wearing in the world beyond her Orthodox suburb. She started clandestinely selling life insurance in order to save her "freedom" money. At the age of forty-two, she finally mustered the courage to flee the fundamentalist life that was strangling her soul. Within a week of her escape, Haart founded a shoe brand, and within nine months, she was at Paris Fashion Week. Just a few years later, she was named creative director of La Perla, where she met the man who would become her husband, Silvio Scaglia. Soon she would become co-owner and CEO of Elite World Group, and one of the most powerful people in the fashion industry. Along the way, her four children-Batsheva, Shlomo, Miriam, and Aron-have not only accepted but embraced her transformation. Propulsive and unforgettable, Haart's story is the journey from a world of no to a world of yes, and an inspiration for women everywhere to find their freedom, their purpose, and their voice"--.
new book 2022 spring.
Keywords: Haart, Julia, -- 1971-; Haart, Julia, -- 1971- -- Family; Ex-Orthodox Jewish women -- Biography; Fashion designers -- Biography; Women fashion designers -- Biography; Ultra-Orthodox Jewish women -- New York (State) -- Monsey -- Social conditions; Women's rights -- Religious aspects -- Judaism